Prevalence and Risk Factors of Stunting among Children Under Five Years of Age in North Sumatra, Indonesia - Diana; Amenda Paswida Sebayang; Evawany Y Aritonang (Media of Health Research, 2026)
Stunting remains a major public health problem among children under five years of age in Indonesia, including North Sumatra Province. This study aimed to analyze the prevalence and identify the risk factors associated with stunting among children under five years of age in North Sumatra, Indonesia. This research employed an analytical cross-sectional design using secondary data obtained from the Indonesian Nutritional Status Survey (SSGI) and related demographic data. The study population consisted of children aged 0–59 months in North Sumatra. Data were analyzed using descriptive statistics, Chi-square tests, and binary logistic regression analysis with a significance level of p < 0.05. The results showed that the prevalence of stunting among children under five years of age in North Sumatra was 27.8%, indicating that stunting remains a serious public health concern. Bivariate analysis revealed significant associations between stunting and several factors, including low birth weight, low maternal education, non-exclusive breastfeeding, inadequate sanitation, and low household income (p < 0.05). Multivariate logistic regression analysis demonstrated that low household income was the most dominant risk factor associated with stunting (AOR = 2.67; 95% CI: 1.81–3.94). The study concludes that stunting among children under five years of age in North Sumatra is influenced by multidimensional factors involving socio-economic conditions, maternal characteristics, child feeding practices, and environmental sanitation. Integrated, multisectoral interventions are needed to reduce stunting prevalence and improve children's nutritional status in North Sumatra.